Performance of explosives and new developments : workshop hosted by Fragblast 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November, 2012 /: workshop hosted by Fragblast 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November, 2012. (©2013) - Unknown
No abstract available